PRODUÇÃO E MANUTENÇÃO DE AFILHOS EM TRIGOS: ASPECTOS GENÉTICOS, FISIOLÓGICOS E DE MANEJO - Sartori, Cesar O.; Silva, José A. G. d.; Maixner, Adriano R.; Carbonera, Roberto; Fernandes, Sandra B. V.; Uhde, Leonir T.; Berto, Jorge; Garcia, Dagmar C. (Salão do Conhecimento, 2013)
Resumo